Activity Choice in Rural Non-farm Employment (RNFE): Survival versus accumulative strategy - Sosina Bezu; Christopher B. Barrett; Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
This paper examines the nonfarm employment choice of individuals using panel data from Ethiopia that covers the period 1994-2004. Non-farm activities that require more resources in the form of skill or capital yield higher returns but employ proportionately fewer people. Women have lower participation rate than men, and those women who participate are often engaged in low-return activities. The econometric results suggest that the factors that influence individuals' decision to participate in non-farm employment differ for the different types of activities. Determinants of participation in high-return activities are dominated by capacity variables. Determinants of participation in low-return activities are dominated by push factors. Education is the only factor that has the same (positive) impact on the likelihood of participation in all types on non-farm employment. Education was also found to have more impact on participation of women.
Keywords: C23; D13; J24; J62; 330; Non-farm; off-farm; non-agriculture; income diversification; Ethiopia